# Thread: Use implicit differentiation to prove the power rule

1. ## Use implicit differentiation to prove the power rule

Let y = x^(a/b) for integers "a" and "b". Raise both sides to the "bth" power and use implicit differentiation to prove the power rule y' = (a/b)x^(a/b-1).

y^b=x^a
b*y^(b-1)*y'=a*x^(a-1)
y'={a*x^(a-1)}/{b*y^(b-1)}
y'=(a/b)*x^(a-1)/x^(a*(b-1)/b)
y' = (a/b)x^(a/b-1)

3. ## Confused

What exactly happened to the b*y in the 3rd step to the 4th step? Why did the y variable disappear?

4. Hello, erimat89!

I'll do it in LaTex . . .

Let $y \:=\: x^{\frac{a}{b}}$ for integers $a\text{ and }b$
Raise both sides to the power $b$ and use implicit differentiation
to prove the power rule: . $y' \:=\:\frac{a}{b}\!\cdot\!x^{\frac{a}{b}-1}$

We have: . $y \;=\;x^{\frac{a}{b}}$ .[1]

Raise to the $b^{th}$ power: . $y^b \:=\:x^a$ .[2]

Differentiate implicitly: . $by^{b-1}y' \;=\;ax^{a-1} \quad\Rightarrow\quad y' \;=\;\frac{a}{b}\cdot\frac{x^{a-1}}{y^{b-1}}

$
.[3]

Divide [2] by $y\!:\;\;y^{b-1} \:=\:\frac{x^a}{y}$

Substitute [1]: . $y^{b-1} \:=\: \frac{x^a}{x^{\frac{a}{b}}} \:=\:x^{a-\frac{a}{b}}$

Substitute into [3]: . $y' \;=\;\frac{a}{b}\cdot\frac{x^{a-1}}{x^{a-\frac{a}{b}}} \quad\Rightarrow\quad\boxed{ y' \;=\;\frac{a}{b}\!\cdot\!x^{\frac{a}{b}-1}}$

b goes in the (a/b)
y = x^(a/b) that why it disappear

6. ## Thanks

Thanks for your help guys I'm finding the calculus concepts to be relatively easy but I obviously haven't mastered the algebra skills that are required to solve calculus related problems which is the reason I'm having such a hard time.

,

,

### implicit differentiation with power rule

Click on a term to search for related topics.